VALIDITY OF GRAY SCALE ULTRASONOGRAPHY IN DIAGNOSIS OF CHRONIC LIVER DISEASE OF VIRAL ETIOLOGY - Riaz, Shaista; Khokhar, Riaz Ahmed; Farooq, Ashraf (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine validity of gray scale ultrasonography in diagnosis of chronic liver disease of viral etiology.Study Design: Validation study.Place and Duration of Study: Medical departments of Rawalpindi Medical College and Allied Hospitals, Rawalpindi in collaboration with Radiology and Pathology departments from 16th June 2008 to 16th Dec 2008.Material and Methods: A sample of 75 patients with polymerase chain reaction (PCR) positive for hepatitis B and C comprising of 33 male and 42 female in the age groups of 19 to 58 years was taken for the study. The patients fulfilling the inclusion criterion were subjected to abdominal ultrasound. Later on findings were confirmed by histopathological findings. The patients were subjected to greyscale ultrasonography in the three parameters of; Edge in terms of sharp, slightly blunted edge, moderately blunted edge and grossly blunted edge; Surface on terms of smooth, slightly irregular, moderately irregular and markedly irregular; Parenchymal texture in terms of fine, slightly coarse, moderately coarse and markedly coarse. For histological examination percutaneous liver biopsy specimens were obtained from the anterior segment of the right lobe in each patient under the guidance of ultrasound. Histopathological grading was distributed over 5 category scales, i.e. “No fibrosis; Fibrosis portalexpansion; Bridging fibrosis; Bridging fibrosis with lobular degeneration and Cirrhosis”.Results: Statistical analysis of the current study revealed that; overall diagnostic accuracy of ultrasound as 86.67% as comparable with gold standard biopsy. Sensitivity was found to be 92.98 %, and Specificity 66.67 %. Positive predictive value was 89.83% and negative predictive value was 75.0% in comparison with gold standard of liver biopsy.Conclusion: The study concludes that ultrasound is equally reliable and dependable technique for the diagnosis of chronic liver disease of viral etiology as compared to histopathological grading.